COMPARISON OF PHYSICAL PROPERTIES AND RATE OF RIFAMPICIN DISSOLUTION IN FIXED DOSE COMBINATION 2FDC TABLET AGAINST TO RIFAMPICIN TABLET - Normalitasari Ayu Damayanti; Widyasari Putranti; Deasy Vanda Pertiwi (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: The World Health Organization (WHO) has recommended using fixed dose combination (FDC) for tuberculosis treatments as it can improve patient compliance and prevent drug resistance. A combination of rifampicin and isoniazid can cause reductions in concentration of each drug because the rifampicin is labile and can not be mixed with all three other TB drugsObjective: This study is aimed to understand effects of the combination of both physical properties and dissolutions of rifampin. Methods: This laboratory study observed rifampicin tablets and combination tablets of rifampicin and isoniazid (2 FDC) by testing physical properties of the tablets and dissolution tests. Friability test was conducted by using friability tester, hardness test was by hardness tester, disintegration test was by disintegration tester and dissolution test was by dissolution tester type 1 (basket). Its data were analysed by Mann Whitney test. The data had value if p<0.05 with CI 95%.Results: This study found that each tablet of rifampicin and 2 FDC tablets respectively had averages of 0.25% and 0.14% of brittleness, 11.07 kg and 10.19 kg of hardness, 2 minutes 1 second and 10 minutes 9 seconds of disintegration time. Consequently, the generic rifampicin tablets were more fragile but harder and faster to crumble than the 2 FDC tablets, in which their mean values were DE45 92.03% and 93.94%. Based on statistical test of Mann Whitney on the rifampicin tablets and 2 FDC, there were no significant differences of hardness test result and mean DE45 0.076(p>0.05 ), while there were significant difference of fragile test result and disintegration time 0.015(p<0.05).Conclusion: The combination of rifampicin and isoniazid in tablet 2 Fixed Dose Combination (2 FDC) had no effects on the dissolution rates of rifampicin, but they had effects on some parameters of physical property test of the tablets.